El tapiz amarillo: una ficción viva (2020)
The Yellow Wallpaper is a graphic adaptation of the story by Charlotte Perkins Gilman. This takes the act of writing as a search for female action and highlights the need to capture a facet of the female experience, in the search for autonomy and independence in the middle of a period of confinement. It places special emphasis on subjectivities, and our way of seeing and living the world as form of resistance. The graphic novel is used as the medium to explore themes, symbols and metaphors and visually expand them in a way that presents this story through a different language.